(3-aminopropyl) triethoxysilane grafted poly(dopamine)@Fe3O4 nanoparticles and their epoxy composites for functional application. (15th July 2019) - Zhang, Yang; Zhang, Zhenqian; Li, Jingyu; Sui, Guoxin
Abstract: The uniform dispersion of Fe3 O4 nanoparticles and strong interfacial bonding with epoxy matrix are crucial for Fe3 O4 /epoxy composite with enhanced mechanical and thermal properties. Cube pure Fe3 O4 nanoparticles (PF NPs) by poly (dopamine) (PDA) coated and (3-aminopropyl) triethoxysilane (APTES) grafted (PAF NPs) are successfully prepared via co-precipitation and seed polymerization method with an aim to enhance the dispersion and interfacial bonding with the epoxy matrix. The tensile strength of PAF/epoxy (1 wt%) increases from 57.8 MPa to 65.5 MPa (a rise scope of almost 13.3%) compared to pure epoxy. The thermal stabilities of PAF/epoxy composites with various PAF contents (1 wt%, 2 wt%, 3 wt%) are higher than that of pure epoxy. The saturation magnetization (Ms) of PAF/epoxy increases from 0.125 to 0.7 emu/g with PAF loading contents increasing from 0.5 to 3 wt%. The results suggest that dispersion and interfacial bonding of nanoparticles make a pivotal contribution to the enhanced performances of composites. Graphical abstract: Image 1 Highlights: APTES grafted poly (dopamine)@Fe3 O4 nanoparticles and their epoxy composites were fabricated. Improved the dispersion of PAF and interfacial bonding with the epoxy matrix were achieved. Enhanced mechanical and thermal properties of PAF/epoxy composites were realized.